Antibacterial effect of pineapple (Ananas comosus) extract towards Staphylococcus aureus - Loon, Yong Ker; Satari, Mieke Hemiawati; Dewi, Warta (Faculty of Dentistry Universitas Padjadjaran, 2018)
Introduction: Staphylococcus aureus is one of the important medical pathogens which have been recognised for many years as a remedyfor a wide case of oral infections. Nowadays, the use of herbal remedy for reducing bacteria in the oral cavity has been implemented widely due to thefewer side effects. Therefore, researchershave been findingwaysto use pineapple in dentistry to prevent many cases of oral diseases. The purpose of this study was to prove that pineapple extract indifferent concentration had the potential as an antibacterial agent towards Staphylococcus aureus. Methods: The study was an experimental laboratory conducted by determining the minimum inhibitory concentration of pineapple (Ananas comosus) with thetwo-fold serial dilution methods. Results:The The Minimum Inhibitory Concentration (MIC) of the pineapple extract was 1.56%-0.78%. Conclusion: The pineapple extract had anantibacterial effect towards Staphylococcus aureus due to the bromelain compound and its phytochemical factor such as Vitamin C and flavonoid.